The components of evaluating the effectiveness of factors affecting the academic silence of secondary school students: Thematic analysis approach - Mohammad Ali Pirkamali; Hasan Rahimi; Ahmad Aryainasab; Nematollah Pirkamali; Mahdiye yahyavezhad (مطالعات روانشناسی تربیتی)
One of the important foundations in the teaching and learning process is the educational interactions that provide the basis for improving education, academic silence is a psychological phenomenon that prevents the interaction and active participation of students in the classroom. Therefore, it leads to a decrease in the effectiveness of teaching in educational environments. The aim of the current research is to know the factors affecting the academic silence of high school students in educational environments. The method of the current research is content analysis, the study population of this research was all those involved in education and stakeholders in the secondary school of Zahedan city. Participants in the research were selected through purposeful criterion-based sampling and the data collection process continued until theoretical saturation was reached. Participants in the research included 15 middle school teachers and 9 students. The data collection tool in this research is a semi-structured interview. Data collection was done using Max Kyuda software. The theme analysis approach in this research was the theme network approach. In order to check the reliability and originality, the criteria of Goba and Lincoln (1980) method were used. The analysis of the results shows four main dimensions affecting students' silence in the classroom, including individual factors, educational factors, structural factors, and cultural factors. According to the results, it can be concluded that students' academic silence depends on various factors that need attention.